Catastrophic Brain Aspergillosis after Liver Transplantation. (15th February 2021) - Abbasi, Mohammadmahdi; Ardakani, Shirin Shams; Fakhar, Nasir; Eshaghi, Hamid; Alimadadi, Hosein; Faghihi, Toktam; Gharib, Behdad; Sharifzadeh, Meisam; Safaei, Masoomeh
Abstract : Background . Liver transplantation has many complications. Because of receiving immunosuppressive regimens, infectious complications in these patients may have fatal results. Aspergillosis in solid organ recipients is one of the most common fungal infections that usually occur 1 month after transplantation. Aspergillus infection mainly involves the lungs. Although the central nervous system may get involved due to hematogenous spreading from lungs, isolated central nervous system involvement is rarely reported. Case Presentation . The patient was an 8-year-old boy, with a case of Wilson disease, who underwent liver transplantation due to acute fulminant hepatic failure. Four days after the surgery, he was affected by fever, agitation, loss of consciousness, hemiparesis, and focal seizure. Brain MRI showed abscess formation, whereas chest X-ray was normal. Intravenous antibiotics were initiated but the patient's condition was not improving; therefore, surgical drainage of the abscess was performed. The pathological investigation was compatible with aspergillosis. Antifungal therapy with voriconazole was administrated. His symptoms were resolved but unfortunately, brain lesions caused persistent vegetative state. Discussion . Aspergillus is a ubiquitous organism that mainly occurs in immunocompromised patients. Aspergillosis could be prevented by environmental modification such as installing high-efficiency particulate air filters. Chemoprevention with triazoles, echinocandins, and polyenes is also effective. Voriconazole is the drug of choice for aspergillosis treatment. Although voriconazole is a highly effective antifungal drug, cerebral aspergillosis is often fatal.